Expression Analysis of Pyrenophora teres f. maculata-Responsive Loci in Hordeum vulgare - Habachi-Houimli,Yosra (2019)
Abstract Pyrenophora teres f. maculata is the causal agent of barley spot form net blotch (SFNB), a major stubble-borne disease in many barley-growing areas worldwide. In plants, the Nucleotide-Binding Site-Leucine-Rich Repeat (NBS-LRR) gene family functions in immunity against a variety of pathogens and pests. From a pre-established set of NBS-type resistance gene candidates, we have selected three candidate genes, HvNBS10, HvNBS72 and HvNBS85, to analyze their possible involvement in P. teres f. maculata resistance. The studied genes were mapped on chromosomes 5H and 7H. Expression profiles using qRT-PCR, 48 hours after infection by P. teres. f. maculata, revealed that the transcription of all genes acted in the same direction (down-regulation) in both resistant and susceptible cultivars, although they showed a variation in transcript dosage. This result suggests that coordinated transcriptional responses of multiple barley NBS genes would be required to an efficient response against P. teres f. maculata. Moreover, the phylogenetic analysis revealed that the studied barley candidate R genes were characterized by a high homology with the barley Nbs2-Rdg2a gene conferring resistance to the fungus Pyrenophora graminea, suggesting a common origin of P. graminea and P. teres resistance genes in barley, following pathogens evolution. The genes characterized in the present study hold potential in elucidating the molecular pathways and developing novel markers associated with SFNB resistance in barley.